Study of Stress Cracking Corrosion resistance of oil Storage tanks - Deema Ali; Fadi Mtawaj; Ahmad Salamah (Tishreen University, 2024)
In this research, the effect of adding some types of inorganic fillers (aluminum oxide, calcium carbonate) on the mechanical and chemical properties of epoxy coatings used to protect the internal surfaces of oil tanks was studied. To achieve this goal, two types of samples were prepared: steel samples and polymeric samples. Polymeric samples were prepared from epoxy with the addition of different percentages of filler, and the surface hardness of these samples were measured, while the steel samples were painted with epoxy paints different from each other in type and percentage of filler, These samples were subjected to chemical corrosion and tensile experiments, and microscopic images of the samples were taken before and after chemical immersion. The results showed an improvement in the mechanical properties and corrosion resistance properties of the developed coating with an increase in the reinforcement ratio. They also showed that the aluminum oxide-reinforced coating was superior to all coatings by 15%.